Investigating the efficacy of a self-directed parenting intervention to reduce risky behaviors among college students: Study protocol for a multi-arm hybrid type 2 randomized control trial - Brittany Rhoades Cooper (Contemporary Clinical Trials Communications, 2020)
Background: Early adulthood is a critical developmental period when many youth transition from living at home to the relative autonomy of college. This transition results in increased opportunity for positive growth and identity development – and for risky substance use and sexual behaviors. Parents continue to influence young adult behavior even from a distance; however, few studies have rigorously tested parent-college student interventions. Methods: This multi-arm hybrid type 2 trial tests the short- and long-term efficacy of a self-directed handbook for parents of first-year college students. In the summer before college, parent-student dyads are randomly assigned to one of three conditions: control, Parent Handbook, or Parent Handbook Plus. Handbook parents receive encouragement via phone calls to read the handbook and complete activities with their student before leaving for college. Handbook Plus parents also receive booster messages targeted at risky or stressful times. Participants complete surveys of intervention-targeted knowledge, attitudes, and behaviors at baseline and four months after baseline. Students complete three additional surveys at nine, 16, and 21 months after baseline. Dyads in the intervention conditions also reported on handbook utilization, perceived usefulness, and engagement with intervention materials. Discussion: Self-directed family interventions may be a feasible strategy for involving parents of college students. This trial aimed to determine: 1) the efficacy of a self-directed handbook intervention for parents of first-year college students, including whether the addition of periodic booster messages enhanced efficacy; and 2) how variations in handbook utilization, perceived usefulness, and engagement were linked to student outcomes.